Immunogenicity of poliovirus vaccines in chronically malnourished infants: A randomized controlled trial in Pakistan. Issue 24 (4th June 2015) - Saleem, Ali Faisal; Mach, Ondrej; Quadri, Farheen; Khan, Asia; Bhatti, Zaid; Rehman, Najeeb ur; Zaidi, Sohail; Weldon, William C.; Oberste, Steven M.; Salama, Maha; Sutter, Roland W.; Zaidi, Anita K.M.
Abstract: Reaching high population immunity against polioviruses (PV) is essential to achieving global polio eradication. Efficacy of oral poliovirus vaccine (OPV) varies and is lower among children living in tropical areas with impoverished environments. Malnutrition found as a risk factor for lower serological protection against PV. We compared whether inactivated polio vaccine (IPV) can be used to rapidly close the immunity gap among chronically malnourished (stunted) infants in Pakistan who will not be eligible for the 14 week IPV dose in routine EPI schedule. A phase 3, multicenter 4-arm randomized controlled trial conducted at five Primary Health Care (PHC) centers in Karachi, Pakistan. Infants, 9–12 months were stratified by length for age Z score into chronically malnourished and normally nourished. Infants were randomized to receive one dose of either bivalent OPV (bOPV) alone or bOPV + IPV. Baseline seroprevalence of PV antibodies and serum immune response to study vaccine dose were assessed by neutralization assay. Vaccine PV shedding in stool was evaluated 7 days after a bOPV challenge dose. Sera and stool were analyzed from 852/928 (92%) enrolled children. At baseline, the seroprevalence was 85.6% ( n = 386), 73.6% ( n = 332), and 70.7% ( n = 319) in malnourished children against PV types 1, 2 and 3 respectively; and 94.1% ( n = 448), 87.0% ( n = 441) and 83.6% ( n = 397) in the normally nourished group ( p < 0.05). Children had previously received 9–10 doses of bOPV (80%) or tOPV (20%). One dose of IPV + bOPV given to malnourished children increased their serological protection (PV1, n = 201, 97.6%; PV2, n = 198, 96.1% and PV3, n = 189, 91.7%) to parity with normally nourished children who had not received IPV ( p = <0.001). Seroconversion and boosting for all three serotypes was significantly more frequent in children who received IPV + bOPV than in those with bOPV only ( p < 0.001) in both strata. Shedding of polioviruses in stool did not differ between study groups and ranged from 2.4% ( n = 5) to 7.1% ( n = 15). In malnourished children the shedding was reduced after bOPV + IPV compared to bOPV only. Chronically malnourished infants were more likely to be unprotected against polioviruses than normal infants. bOPV + IPV helped close the immunity gap better than bOPV alone.